Horizontal Integration with Emphasize on IoT: from Tropical Functional Food Research to Teaching Excellence - Rahmadi, Anton; Rohmah, Miftakhur; Sagena, Unis (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The laboratory is a research powerhouse being a transportation membrane to propagate new and proven knowledge. This paper aims to descriptively disseminate the concept of horizontal integration from research in tropical functional food resources to teaching excellence framework with an emphasize on IoT Technology. The five-stage framework includes (1) vision internalization, (2) persistence propagation, (3) new technology adaptation, (4) extending collaboration, and (5) outcome integration. The vision internalization stage produces a better understanding of the big picture and systematic approach required, including the division of experiments to research attendance. The experience is then brought to Research Methodology and Research Design classes. In the second stage, persistence propagation may be better translated to relentlessly solving the problem and to increase the laboratory power. The persistence propagation also includes providing fail-safe and verification procedures of possibly dubious results produced in the laboratory. In the end, it may improve operating procedures or methods in a laboratory manual. The movement of open hardware makes it possible for faster technology adaptation to food-laboratory. For example, measuring functional food material drying kinetics is now quickly adopted as a result of recent IoT technology. In a later stage, IoT is integrated into the closest courses, i.e., Introduction to Computer or Programming in Food Technology. The research may reach a milestone that requires expansion and sophisticated equipment beyond the capacity of the laboratory. Therefore, collaboration is needed between laboratories within the university or greater. Students are prepared to conduct functional food research in partner laboratories; hence, the requisite bench skills are better taught. The last stage happens when new and related knowledge is accumulated, i.e., umbrella research in functional food produces several publications and theses. Researchers may visit and align the current curriculum in the subject of Functional Food Technology. In summary, the horizontal integration with an emphasize on IoT Technology results in a unique set of research-teaching excellence framework that is incrementally developed.